Glomus tumor presenting as complex regional pain syndrome of the left upper limb: a case report. (December 2015) - Macharia, Chege; Nthumba, Peter
Abstract Background Glomus tumors of the hand are rare, benign but debilitating neoplasms arising from the neuromyoarterial glomus body. They may present a diagnostic dilemma, and take years with multiple consultations and investigations before an appropriate diagnosis is made, but once a diagnosis is made, surgical excision is curative. Case presentation This is a case presentation of a 35-year-old African man who presented with complex regional pain syndrome of his left upper extremity, whose genesis was found to be a glomus tumor of the pulp of his left middle finger. Surgical excision resulted in resolution of the chronic regional pain syndrome and a return to a normal lifestyle. Chronic regional pain syndrome is a rare presentation of a glomus tumor, which has only been previously reported in patients with neurofibromatosis type 1, and one patient who did not have neurofibromatosis. Conclusions Patients with glomus tumors may spend many years in pain and distress because of misdiagnosis. Sensitization and education of both the public and health care workers will help in early diagnosis and treatment of this otherwise potentially disabling pathology for which surgical excision is curative.